A multimetallic iron(ii)–lithium complex as a catalyst for ε-caprolactone polymerization. Issue 40 (7th April 2016) - Geng, Chao; Peng, Ying; Wang, Lijuan; Roesky, Herbert W.; Liu, Kaipeng
Abstract : Treatment of the lithium salt of β-ketimine with FeCl2 (THF)1.5 in the presence of LiN(SiMe3 )2 and water affords the multimetallic iron(ii )–lithium complex1, [(L Me )2 Fe]3 Li2 O [where L Me = MeC(O)CHC(NMe)Me]. Abstract : Treatment of the lithium salt of β-ketimine with FeCl2 (THF)1.5 in the presence of LiN(SiMe3 )2 and water affords the multimetallic iron(ii )–lithium complex1, [(L Me )2 Fe]3 Li2 O [where L Me = MeC(O)CHC(NMe)Me]. In complex1 three separated (L Me )2 Fe units are bound together by one Li2 O species, which leads to the formation of an interesting Fe3 Li2 O core structure. Complex1 can be used as a single-component initiator for the ring-opening polymerization of ε-caprolactone at room temperature, achieving a monomer conversion of 98% within 100 min, and a narrow molecular weight distribution (PDI = 1.28) of the resulting polymer.